(untitled) (Bangladesh Journal of Medical Science, 2021)
Introduction: If the football lessons with children take into account their strength of thenervous system in the process of excitation, the effectiveness of such activities will be higher. Objective: Study of the effect of the nervous system of players on the ability to rationally relax their muscles. Method: 44 athlete’s aged 13-14 years took part in the pedagogical experiment.22 young footballers were engaged in the experimental methodic, which is based on the useof different components of the load, for players with a strong nervous system (11 people) theload was intense, and for players with a weak nervous system (11 people) - volume. Other 22athletes were in the control group. Results: After 7 months of research, we saw a significantimprovement in the ability to relax the muscles in children aged 13-14 years, who trainedaccording to our methodic. Children who have a strong nervous system, improved performancein the test “juggling the ball” from 4.1±0.8 times to 6.5±1.1 times (P<0.05), and players with aweak nervous system – from 3.8±1.3 times to 5.4±1.4 times (P<0.05). In the control group, thechanges were positive but unreliable (P> 0.05). Conclusion: If the lessons with children use adifferentiated method, which is based on the typology of the nervous system, the performanceof children will improve significantly. The use of this method will improve the technicalperformance of athletes and improve the quality of the training process. Bangladesh Journal of Medical Science Vol.20(1) 2021 p.58-61